Integrasi Pembelajaran Ips Berbasis Pendidikan Nilai Agama Untuk Meningkatkan Kompetensi Pengetahuan Dan Kompetensi Sikap - Himmatus Sa'adah (Universitas Negeri Surabaya, 2023)
Abstrak Penelitian ini bertujuan untuk menganalisis kelayakan dan keefektifan hasil pengembangan model integrasi pembelajaran IPS berbasis pendidikan agama, menggunakan Four-D Model Thiagarajan. Penelitian ini sampai tahap disseminate yaitu tahap penyebaran kepada MGMP guru mata pelajaran IPS kabupaten Sidoarjo. Penelitian dilakukan di MTs Fadllillah. Model pembelajaran IPS berbasis pendidikan agama merupakan representasi untuk pembelajaran berbasis agama yang menggambarkan karakteristik keterpaduan IPS dari awal hinga akhir. Dilakukan pengembangan pada : 1) kajian manusia tempat dan lingkungannya sebagai materi berbasis agama; 2) pengorganisasian kegiatan pembelajaran merujuk pada pembelajaran konstektual; dan 3) evaluasi pencapaian kompetensi siswa secara otentik. Berdasarkan penilaian ahli, model pembelajaran dinyatakan layak digunakan dengan skor tertinggi 89,5%. Berdasarkan hasil perhitungan rata-rata ketuntasan individu pada pretest sebesar 30,4% siswa dinyatakan tuntas dan posttest sebesar 78,2% siswa dinyatakan tuntas. Berdasarkan perhitungan tersebut terjadi kenaikan signifikan yaitu sebesar 47,8%. Oleh sebab itu model pembelajaran dinyatakan efektif untuk meningkatkan kompetensi pengetahuan dan kompetensi sikap siswa. Kata Kunci: Model Pembelajaran, IPS, Pendidikan Agama. Abstract This study aims to analyze the feasibility and effectiveness of the results of integrating a social studies learning model based on religious education, using the Four-D Thiagarajan Model. This research reached the disseminate stage, namely the dissemination stage to the MGMP for social studies teachers in Sidoarjo district. The research was conducted at MTs Fadllillah Tambak Sumur. The social studies learning model based on religious education is a representation for religion-based learning that describes the characteristics of the integration of social studies from the beginning to the end. Development is carried out on 1) Study of the human being, place and environment as religious-based material; 2) organizing learning activities refers to contextual learning; and 3) evaluation of student competency achievement authentically. Based on expert judgment, the learning model was declared suitable for use with the highest score of 89.5%. Based on the results of the calculation of the average individual completeness in the pretest of 30.4% of students declared complete and posttest of 78.2% of students declared complete. Based on these calculations there was a significant increase of 47.8%. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes. Keywords: Learning Model, Social Studies, Religion Education.